2021
DOI: 10.1101/2021.06.12.21258813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of tozinameran (BNT162b2) mRNA vaccine on kidney transplant and chronic dialysis patients: 3-5 months followup

Abstract: Background: Determining the humoral immunogenicity of tozinameran (BNT162b2) vaccine in patients requiring chronic renal replacement therapy, and its impact on COVID-19 morbidity several months after vaccination, will guide risk assessment and subsequent changes in vaccination policy. Methods: In a prospective post-vaccination cohort study with up to 5 months follow-up we studied outpatient dialysis and kidney transplant patients and respective healthcare teams. Outcomes were anti S1/S2 antibody response to v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…We have previously noted that with a most recent antibody level at or above 59 AU/ml no post-vaccination cohort participant became infected with COVID-19, suggesting a protective cutoff 5 . Figure 2b shows that prior to boosting, this level was achieved by 80% of controls, 35% of dialysis patients and 10% of transplant patients, while 8-54 days after booster injection respective rates were 100%, 93% and 58%.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously noted that with a most recent antibody level at or above 59 AU/ml no post-vaccination cohort participant became infected with COVID-19, suggesting a protective cutoff 5 . Figure 2b shows that prior to boosting, this level was achieved by 80% of controls, 35% of dialysis patients and 10% of transplant patients, while 8-54 days after booster injection respective rates were 100%, 93% and 58%.…”
Section: Resultsmentioning
confidence: 91%
“…Patients needing chronic renal replacement therapy are at risk for severe COVID-19 3 and have been shown to mount a lesser humoral response to mRNA vaccination 4 . In our single center cohort we have observed that reduced vaccine-elicited antibody levels in dialysis and kidney transplant patients associated with increased infection rates 5 . Herein, we describe the short term impact of booster administration in these patients, amidst a third wave of infections and deaths currently experienced in Israel primarily by the Delta variant, possibly amplified by waning immunity ( Figure 1 ) 6 .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Patients needing chronic renal replacement therapy are at risk for severe COVID-19 and have been shown to mount a lesser humoral response to mRNA vaccination [ 2 ]. In our single-center cohort we observed that reduced vaccine-elicited antibody levels in dialysis and kidney transplant patients were associated with increased infection rates [ 3 ]. Herein, we describe the short-term impact of booster administration in these patients, amidst a third wave of infections and deaths currently experienced in Israel primarily by the Delta variant, possibly amplified by waning immunity (Online Resource 1).…”
mentioning
confidence: 99%
“…Prior to initiation of vaccination we launched the COVID-19 mRNA Vaccine Immunogenicity in patients with end stage Renal Disease (COVIReD) prospective cohort study designed to investigate the long-term kinetics and implications of antibody response to COVID-19 vaccine and infection in this vulnerable population. The study was approved by the local ethical Committee and its methods and preliminary results have been recently published [ 3 ]. In this update, we report patients’ humoral responses to booster vaccination.…”
mentioning
confidence: 99%